2017
DOI: 10.1002/phar.1899
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Obesity: Pharmacokinetic Alterations and Effects on Antimicrobial Dosing

Abstract: Limited data exist for appropriate drug dosing in obese children. This comprehensive review summarizes pharmacokinetic (PK) alterations that occur with age and obesity, and these effects on antimicrobial dosing. A thorough comparison of different measures of body weight and specific antimicrobial agents including cefazolin, cefepime, ceftazidime, daptomycin, doripenem, gentamicin, linezolid, meropenem, piperacillin-tazobactam, tobramycin, vancomycin, and voriconazole is presented. PubMed (1966-July 2015) and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…Overweight and obesity are increasingly prevalent among children, which creates specific dilemmas in drug dosing [ 35 ]. There were no specific recommendations available for FQ dosing for overweight and obese children in our centers, during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Overweight and obesity are increasingly prevalent among children, which creates specific dilemmas in drug dosing [ 35 ]. There were no specific recommendations available for FQ dosing for overweight and obese children in our centers, during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Although we found only one prescription had followed such a metric, individualized dosing by metrics of body size may be more feasible in overweight/obese children than common pediatric dosing strategies by TBW or fixed dose by age , . A reflection of the findings in this study, therefore, is that metrics of body size does not seem to be implemented in the clinic unless they have been “transformed” into clinical usefully guidelines.…”
Section: Discussionmentioning
confidence: 79%
“…Although we found only one prescription had followed such a metric, individualized dosing by metrics of body size may be more feasible in overweight/obese children than common pediatric dosing strategies by TBW or fixed dose by age. [5][6][7][8][9][10]16,17,19,20,23,[34][35][36][37][38][38][39][40][41][42][43][44][45][46] A reflection of the findings in this study, therefore, is that metrics of body size does not seem to be implemented in the clinic unless they have been "transformed" into clinical usefully guidelines. 48 In this study, we found that the capping dose was common practice, when the dose exceeded the maximum recommended adult dose.…”
Section: Overweight/obesitymentioning
confidence: 99%
“…We believe this approach to the question of the effect of obesity on drug dosing would identify medications likely to be relevant to general hospital practice. Prior pediatric reviews narrowed their coverage by focusing on one therapeutic category: for example, antimicrobials (86), area of practice (e.g., surgery (87) or emergency medicine (88)), or PK properties of drugs (14). The later major review yielded mostly uncommon drugs.…”
Section: General Critique and Points Of Special Interestmentioning
confidence: 99%